THE EFFECT OF MOBILE LEARNING AND LEARNING STYLES ON STUDENTS’ SCIENTIFIC LITERACY IN SALT HYDROLYSIS CONCEPT - Ucu Cahyana; Irwanto Septian; Erdawati Erdawati (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2020)
This study aimed to determine the effect of mobile learning and learning style on students’ scientific literacy in the salt hydrolysis concept. This research was conducted at Senior High School 42 Jakarta with a sample of 56 students consisting of 28 students with visual learning style and 28 students with auditory learning style. The sample in the study was randomly selected. The research method used was experimental with 2x2 design level treatment and analyzed by Two-Way ANOVA. The results showed that there were differences in scientific literacy between groups of students who used mobile and traditional learning (without considering learning styles) and groups of students who used a combination of consideration of learning styles and mobile learning. The use of mobile learning has a positive effect on scientific literacy outcomes when applied to group visual learning styles. Whereas, in the audio learning style group, the use of mobile learning media provided lower scientific literacy results compared to traditional learning media.